Influence of common bean genotypes and rhizobia interaction for nodulation and nitrogen fixation - Milcheski, Viviane de Fátima; Senff, Sindi Elen; Orsi, Nicole; Botelho, Gloria Regina; Fioreze, Ana Carolina da Costa Lara (Revista de Ciências Agroveterinárias, 2022)
Bacteria from the rhizobia group are able to associate symbiotically with bean crop, forming nodules in the root, in which the biological nitrogen-fixing process occurs. However, the efficiency of this process has been low and it can be attributed to genetic and environmental factors. Thus, the objective of this study was to evaluate the capacity of nodulation of local varieties and commercial common bean cultivars inoculated with a Rhizobium tropici strain used in commercial inoculants and rhizobia isolates from common bean root nodules. The experiment was carried out in a factorial scheme (2x4), in a randomized block design with four replicates. It was tested two local varieties and two commercial cultivars, inoculated with the reference Rhizobium tropici strain CIAT899 and the RBZ14 strain isolated from common bean nodules grown in soils of Southern Brazil, in adapted Leonard-type pots. The CIAT899 strain promoted either higher mass of viable nodules and higher nitrogen accumulation in the aerial part. The black group local variety showed better response than the cultivar TAA Dama for nodule viability, suggesting more efficiency for nodulation. The interaction between genotypes (local varieties and commercial cultivars) and bacteria showed the specificity of the complex symbiotic relationship of biological nitrogen fixation in common bean, requiring further studies of these interactions.